Chandipura virus outbreak in India: A tropical nightmare - Banerjee, Indrajit; Robinson, Jared; Roy, Bedanta; Upreti, Dipesh; Singh, Ashok Pratap; Banerjee, Indraneel (Journal of Biomedical Sciences, 2024)
Chandipura virus (CHPV) is currently implicated in outbreaks of viral encephalitis in rural India. The current outbreak in India has grown to 59 cases, 51 of which have been reported from Gujarat and the remaining from Rajasthan. It is of the utmost importance that all relevant health authorities carefully monitor the ongoing situation to bolster and protect international health security and ensure it is not compromised. Chandipura virus causes febrile disease. After the febrile phase, patients begin to present with neurological symptoms, as the virus is neurotropic in nature and results in encephalitis. No specific treatment for CHPV is available, and the management of cases is chiefly by symptomatic treatment. The Chandipura virus may have global implications. It is of global importance that the relevant authorities handle Chandipura and prevent further transmission.